Does Household Access to Financial Services Help Reduce Poverty in Indonesia? - Yuanita, Ika; Sumiarti, Elni; Yenida, (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims todetermine propensity of household access to financial services and to examine their impact on helping reduce poverty in Indonesia, Nov-2018 until Feb-2019 by the National Socioeconomic Survey (SUSENAS), March 2019, around 315,672 households. To determine the propensity of household access to financial services, we use a probit model integrated with propensity score matching. With a quasi-experimental design, data were analyzed using the average treatment effect on treated (ATT) by household access to financial services (treatment) within 77,602 households with access (treated) and 238,070 households without access (control) to financial services. Estimation of propensity score was used to reduce selection bias of ATT on the outcome variables. The empirical findings show that household poverty status was reduced which would have occurred if they had access to financial services. Accessing financial services as transitory income has a negative impact, thus we conclude it was an unfavorable income. For poor, it is not yet significant enough but has a positive impact on increasing their expenditure per capita a month, averagely. Thus, the decrease or increase in their incomes didn’t increase or decrease their expenditure in the short-run, but in the long-run, it occurred.